The potential use of natural expanded perlite as a flame retardant additive for acrylonitrile-butadiene-styrene based composites - Celen, Utku; Tamer, Yasemin Balcik; Berber, Hale (WILEY, 2024)
This study aimed to reveal the effect of expanded perlite (EP) additive as a flame retardant for acrylonitrile-butadiene-styrene (ABS) copolymer based composites. Before composite preparation, fine powdered EP was characterized by Fourier transform infrared spectroscopy, x-ray diffraction, thermogravimetric analysis, and scanning electron microscopic analyses. Also, maleic anhydride grafted ABS (MAH-g-ABS) with a grafting degree of 3.9 wt% was synthesized and used as a polymeric compatibilizer. ABS/EP composites with different ratios of EP were prepared by a continuous one-step melt mixing method. Thermogravimetric and morphological analysis, tensile tests, limiting oxygen index (LOI) and UL-94 vertical burning tests of the composite materials were investigated. EP significantly decreased the decomposition rate of ABS and promoted char formation. EP provided a UL-94 V-1 flammability rating with great fire resistance and self-extinguishing properties to the ABS matrix without any melt dripping. The LOI of ABS was greatly improved, reaching a value of 28.5% by adding only 5 phr EP. Zinc borate (ZB) also played a significant role in enhancing thermal stability and flame retardancy by creating a good synergism with EP. The composite containing 5 phr ZB showed a flame retardant grade of UL-94 V-0 and an LOI value of 27.5%
Keywords: acrylonitrile-butadiene-styrene; expanded perlite; halogen-free flame retardant; polymer composite; zinc borate; MECHANICAL-PROPERTIES; THERMAL-STABILITY; DENSITY; NANOPARTICLES; FLAMMABILITY; FIBER; Chemistry; Materials Science; Polymer Science